2020
DOI: 10.1177/0031512519900055
|View full text |Cite
|
Sign up to set email alerts
|

Sports Participation Correlates With Academic Achievement: Results From a Large Adolescent Sample Within the 2017 U.S. National Youth Risk Behavior Survey

Abstract: This study sought to examine associations between (a) sports team participation; (b) lifestyle behaviors (e.g., sleeping, alcohol, and tobacco use); and (c) dietary behaviors with self-reported academic achievement using data derived from the 2017 U.S. National Youth Risk Behavior Survey. A multistage cluster sampling procedure was employed to obtain a representative sample of U.S. adolescents from among whom the number with usable data was 14,765. We used weighted logistic regression models to examine the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…The current research findings that participation on team sports was independently correlated with academic performance is supported by previous studies ( 16 , 23 , 24 , 29 , 30 ). For example Fox et al ( 23 ) found that team sports participation was positively correlated with higher grade point averages in high school students, which is comparable to this study sample.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The current research findings that participation on team sports was independently correlated with academic performance is supported by previous studies ( 16 , 23 , 24 , 29 , 30 ). For example Fox et al ( 23 ) found that team sports participation was positively correlated with higher grade point averages in high school students, which is comparable to this study sample.…”
Section: Discussionsupporting
confidence: 90%
“…For example Fox et al ( 23 ) found that team sports participation was positively correlated with higher grade point averages in high school students, which is comparable to this study sample. A recently published study by Burns et al ( 16 ) also suggested that more team sports participation in adolescents was associated with better academic performance. In addition, some longitudinal studies also support the research findings ( 18 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…14 Sport participation also provides exposure to social factors that are often not present during unstructured PA. Sports participation provides opportunities to enhance task-specific self-efficacy, personal enjoyment, prosocial behavior, and a sense of social support from coaches and teammates. 15,16 These characteristics of sport participation may lead to improvements in specific aspects of academic performance above and beyond that provided by other modes of PA. 17,18 However, a paucity of work has compared both PA and sports participation on various aspects of academic performance variables while also controlling for important factors at both the child and family level.…”
mentioning
confidence: 99%